Unlocking the power of visual grammar theory: analyzing social media political advertising messages in the 2016 US election. Issue 2 (3rd April 2017) - Friedman, A.; Ron, S.
Abstract: Social media advertisers often use visuals in their ads to capture their audience's attention. Walter and Gioglio (2014) find that social media directly reduces the audience's attention span, which they call the new commodity. In this context, visuals are our new currency. However, the subject of visual grammar theories has not been fully examined in relation to the design of advertising messages found in social media. During the 2016 US presidential election, social media conveyed the two leading candidates' messages. We conduct a comparative analysis to evaluate two leading visual grammar theories, those of Kress and van Leeuwen (2002) and Wilkinson (1999), and report that Kress and van Leeuwen's theory leads to a better in-depth analysis of the visual messages found in two political ads from the U.S. presidential race of 2016.